ANTITOXIC EFFECT OF TAURINE (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
Investigation of single injection of taurine on Lebetina viper’ venom-induced shifts of morpho-functional indices of rats’ peripheral blood was carried out. It was revealed that taurine eliminates negative effects of influence of venom. The results of the investigation allow us to assume that taurine trigger adaptive and compensatory mechanisms of organism in conditions of toxins’ influence.
Keywords: taurine; peripheral blood; venom; compensatory mechanism